Becoming adults: exploring the late ontogeny of the human talus - Figus, Carla; Sorrentino, Rita; Carlson, Kristian J.; Colombo, Antony; Bortolini, Eugenio; Bernardini, Federico; Erjavec, Igor; Hajdu, Tamás; Szeniczey, Tamás; Mateovics-László, Orsolya; Pap, Ildiko; Tuniz, Claudio; et al. (Frontiers in Ecology and Evolution, 2023)
Introduction: The talus plays an important role in receiving and dissipating the forces and linking the leg and the foot. As such, it is of paramount importance to analyze how its morphology, internal and external, changes during late ontogeny and through adolescence. Method: To explore both the external shape and the internal architecture of the talus, Geometric Morphometrics and trabecular analysis have been applied to a sample of 35 tali from modern human juveniles aged between 5 and 15 years old (Middle Neolithic (4800-4500 BCE) to mid-20th century). Results: Results show that, as the overall size of the talus increases, the shape and orientation of talar facets also change. The youngest individuals exhibit a functional talus that is still characterized by a relatively immature shape (e.g., subtly expressed margins of articular surfaces) with articular facets only minimally rotated towards an adult configuration. In adolescents, talar shape has achieved adult form after the age of 11, with all the articular facets and posterior processes well-developed. Considering internal morphology, trabecular bone varies between age classes. While Bone Volume Fraction shifts during the age 5-15 range, Degree of Anisotropy is relatively more stable over the developmental period examined in the study since it exhibits smaller variations between age classes. Discussion: This study examined the late ontogeny of the human talus by considering both internal and external morphology. Results suggest that, although the locomotion has already assumed an adult-like pattern, the exploration of late talar growth may help understand how the talus adapts to changes in locomotor activity and how it responds to the increase in weight. Present results can be used to a better understanding of talar plasticity, improving interpretations of adult human talar form.